2014
DOI: 10.1128/iai.01373-13
|View full text |Cite
|
Sign up to set email alerts
|

Uropathogenic Escherichia coli Modulates Innate Immunity To Suppress Th1-Mediated Inflammatory Responses during Infectious Epididymitis

Abstract: cInfectious epididymitis in men, a frequent entity in urological outpatient settings, is commonly caused by bacteria originating from the anal region ascending the genitourinary tract. One of the most prevalent pathogens associated with epididymitis is Escherichia coli. In our previous study, we showed that semen quality is compromised in men following epididymitis associated with specific E. coli pathovars. Thus, our aim was to investigate possible differences in immune responses elicited during epididymitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
1
15
1
Order By: Relevance
“…In contrast to a study that found high TNF-a in all leukocytospermic patients (Seshadri et al, 2012), a study that investigated uropathogens reported that TNF-a was high only in semen plasma of patients infected with Gram-negative bacteria rather than patients infected with Gram-positive bacteria (Lang et al, 2014). The effect of infection type on the level of seminal plasma cytokines was not investigated in current study.…”
Section: Discussioncontrasting
confidence: 79%
“…In contrast to a study that found high TNF-a in all leukocytospermic patients (Seshadri et al, 2012), a study that investigated uropathogens reported that TNF-a was high only in semen plasma of patients infected with Gram-negative bacteria rather than patients infected with Gram-positive bacteria (Lang et al, 2014). The effect of infection type on the level of seminal plasma cytokines was not investigated in current study.…”
Section: Discussioncontrasting
confidence: 79%
“…To elucidate whether the UPEC-induced acrosome reaction leads to an activation of endogenous sialidases, initiating a subsequent desialylation of spermatozoa, an established epididymitis mouse model was utilized (25). Histopathology in MassonGoldner-stained epididymis demonstrated fibrotic remodeling and interstitial leukocytic infiltration as the most obvious consequences 3 days post-UPEC infection, as shown previously (Fig.…”
Section: Desialylation Of Spermatozoa and Epithelial Cells Is A Consesupporting
confidence: 67%
“…Together with neutrophils and T cells, their numbers increase strongly in infection (25,38,39). It appears therefore likely that soluble neuraminidases may also detach sialic acid residues from the cell surface of immune cells during infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 days after antibiotic treatment [20]. In epididymitis associated with NPEC, semen parameters had recovered to normal after 84 days, in contrast to the permanent impairment seen in UPEC infection [6,21]. Histological examination of tissue obtained from men with chronic epididymitis in this and a previous study point to ductal obstruction as a consequence of epithelial damage and fibrotic remodelling [9].…”
Section: Activin a Induces Fibrotic Transformation In Epididymis Orgamentioning
confidence: 73%